We move together - Fritsch, Kelly; McGuire, Anne, 1981- (AK Press, 2021)
A bold and colorful exploration of all the ways that people navigate through the spaces around them, and a celebration of the relationships we build along the way. We Move Together follows a mixed-ability group of kids as they creatively negotiate everyday barriers, and find joy and connection in disability culture and community. A perfect tool for families, schools, and libraries to facilitate conversations about disability, accessibility, social justice, and community building. Includes a kid-friendly glossary.